Cenário como processo projetual: cartografia para a construção de uma metodologia de design - Santos, Ana Paula Silveira dos (Universidade do Vale do Rio dos Sinos, 2023)
From a strategic design perspective, this thesis investigates scenarios as a process. The main focus is set on building a methodology dedicated to those project processes which are involved in project action, understood as scenario-based project processes, developed at metaproject level. In this context, scenarios are understood as the production of past, present and future narratives. For this purpose, we put into practice processes operated through the concepts of polyphony and the imaginary, which contribute to the occurrence of a presence that is actualised as memory or imagination and made up of multiple voices. We explore the technique of cartography which, in the face of such plurality, finds ways of expressing subjectivities which, in turn, respond to intersubjectivities. Cartography gives voice to affections in their very inception, minimising the restrictions that affect perception when it’s subject to logic and rationality. Thus, our general aim is to propose a methodology for the development of scenario-based project processes whose narratives can potentialize the imaginary and polyphony. In order for the cartographic technique to be able to preserve the subjects’ perceptions about specific realities, the urban reality (more specifically, the city of Porto Alegre – Brazil) is chosen as the locus for observation and record. It is a diverse and dynamic social space, a localised synthesis of contemporary living, which is intrinsically collaborative. The production of knowledge is supported by bibliographical research, by the visual and aural records originating from the cartographies, from the analysis operations and from the collective project practices. This is an empirical inductive, qualitative exploratory research exercise. Therefore, it is by means of the metaproject exercise that the different movements that make up the methodology take shape. The first movement is the collection of the cartographies from the individual cartographers. The second movement exercises the practice of building scenarios based on the cartographies of the first movement. The third movement works on metaprojecting based on the scenario-building activities of the two previous movements. The result of the aforementioned movements and practical processes, are reflections and thought constructions that justify the creative power that resides at the metaproject level, taking into consideration the implementation and practice of the project process. We propose a methodology that deals with scenarios as process, based on cartographic practice.
Keywords: Cartografia; Cenários; Processo; Metaprojeto; Design estratégico; Imaginário; Polifonia; Cartography; Scenarios; Process; Metaproject; Strategic design; Imaginary; Polyphony; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial